Comprehensive Analysis of Perioperative Factors Influencing the Risk of Biochemical Recurrence in Patients with Radical Prostatectomy - Borz, Mihnea Bogdan; Schitcu, Vlad Horia; Crisan, Nicolae; Petrut, Bogdan; Borz, Oliviu Cristian; Borz, Paul Cristian; Duquesne, Igor; Nasri, Jordan; Coman, Ioan (Urology Journal, 2024)
Purpose: To analyze the perioperative factors that influence the risk of biochemical recurrence (BCR) in patients with localized PCa undergoing radical prostatectomy Materials and Methods: A total of 457 patients, operated by 2 surgeons in our high-volume oncological center were included in the initial database. Patients who underwent RP for clinically localized PCa in our clinic from 2016 to 2021 were included in the study. Perioperative data were retrospectively reviewed for this study. Follow-up data including post-operative PSA and adjuvant treatment was prospectively gathered by contacting the patients or from the follow-up consultation. Final database was composed of 366 patients who underwent open or 3D laparoscopic RP. Statistical analysis was performed to emphasize the most powerful parameters that influence the BCR. Results: Accounting for multivariable analysis, 4 parameters were statistically significant: initial PSA (iPSA), Gleason score, vascular involvement and positive surgical margins. For the group of patients with no positive margins, 3 parameters were statistically significant: iPSA above 10,98 ng/mL (AUC=0,71); lymph node involvement and Gleason score. Multivariable Cox regression showed that positive margins and iPSA had a significant impact on the time to BCR. Patients that received adjuvant therapy were excluded from the study. Out of the whole cohort, 27,3% of patients presented BCR. Conclusion: Perioperative factors need to be carefully analyzed and a detailed follow-up needs to be conducted in order to assess the risk of biochemical recurrence, resulting in the optimal time for adjuvant treatment implementation.